(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2019)
The increasing importance of endovascular surgery requires the development of authentic simulation environments to test new endovascular devices and navigation systems. Purpose of this project was the development of a simulator that mimics endovascular procedures as realistic as possible to minimize the use of animal models. Using the technique of rapid prototyping we developed an endovascular simulator with exchangeable 3D-printed real vascular pathologies. The technique of 3D-printing opened the door to produce endovascular simulators with authentic vascular pathologies. This can reduce the use of animals for research purposes.